Synthesis, cytotoxic potential, and molecular docking studies of ortho-carboxamidostilbene analogs - Mohd Azlan Nafiah (Tanjung Malim, 2023)
Synthesis, cytotoxic potential, and molecular docking studies of ortho-carboxamidostilbene analogs by Mohd Azlan Nafiah